A narrative review on inflammaging and late-onset hypogonadism - Xing, Dong; Jin, Yihan; Jin, Baofang (Frontiers in Endocrinology, 2024)
The increasing life expectancy observed in recent years has resulted in a higher prevalence of lateonset hypogonadism (LOH) in older men. LOH is characterized by the decline in testosterone levels and can have significant impacts on physical and mental health. While the underlying causes of LOH are not fully understood, there is a growing interest in exploring the role of inflammaging in its development. Inflammaging is a concept that describes the chronic, low-grade, systemic inflammation that occurs as a result of aging. This inflammatory state has been implicated in the development of various age-related diseases. Several cellular and molecular mechanisms have been identified as contributors to inflammaging, including immune senescence, cellular senescence, autophagy defects, and mitochondrial dysfunction. Despite the extensive research on inflammaging, its relationship with LOH has not yet been thoroughly reviewed in the literature. To address this gap, we aim to review the latest findings related to inflammaging and its impact on the development of LOH. Additionally, we will explore interventions that target inflammaging as potential treatments for LOH.